Kafka's creatures animals, hybrids, and other fantastic beings - Lucht, Marc 1969-.; Yarri, Donna; IG Publishing (Lanham, Md. Lexington Books, 2010)
There are few literary authors in whose work animals and other creatures play as prominent a role as they do in Franz Kafka's. Exploring multiple dimensions of Kafka's incorporation of nonhuman creatures into his writing, this volume is the first collection in English of essays devoted to illuminating this important and ubiquitous dimension of his work. The chapters here are written by an array of international scholars from various fields, and represent a diversity of interpretive approaches.
Contents; Acknowledgments; Chapter 1 Introduction; Chapter 2 Kafka's Hybrids: Thinking Animals and Mirrored Humans; Chapter 3 "Czechs, Jews and Dogs Not Allowed": Identity, Boundary, and Moral Stance in Kafka's "A Crossbreed" and "Jackals and Arabs"; Chapter 4 De-allegorizing Kafka's Ape: Two Animalistic Contexts; Chapter 5 Agents of the Forgotten: Animals as the Vehicles of Shame in Kafka; Chapter 6 The Difficult Task of Being Real: Odradek, the Kittenlamb, and the Historical Individual; Chapter 7 Consolation in Your Neighbor's Fur: On Kafka's Animal Parables. Chapter 8 Crowds, Animality, and Aesthetic Language in Kafka's"Josephine"Chapter 9 Performative Emotion in Kafka's "Josephine, the Singer; or, the Mouse Folk" and Freud's "The Creative Writer and Daydreaming"; Chapter 10 The Power of the Look: Franz Kafka's "The Cares of a Family Man"; Chapter 11 Four Hands Good, Two Hands Bad; Chapter 12 Who Identified the Animal? Hybridity and Body Politics in Kafka's "The Metamorphosis" and Amerika (The Man Who Disappeared); Chapter 13 The Portrait of an Armor-Plated Sign: Reimagining Samsa's Exoskeleton. Chapter 14 Extraterrestrial Kafka: Ahead to the Graphic NovelChapter 15 Index to Kafka's Use of Creatures in His Writings; Index; About the Contributors.
Electronic reproduction.
Keywords: Kafka, Franz -- 1883-1924 -- Criticism and interpretation; Animals in literature; Animals, Mythical, in literature; Human-animal relationships in literature; Electronic books